Chronic exposure to ammonia induces oxidative stress and enhanced glycolysis in lung of piglets. Issue 2 (22nd November 2021) - Qin, Wenhao; Shen, Long; Wang, Qiankun; Gao, Yun; She, Mengqi; Li, Xiaoping; Tan, Zuojun
Abstract: Ammonia is one of the major environmental pollutants in the pig industry that seriously affects the airway health of pigs. In this study, we aimed to investigate the metabolic profiling changes of piglets' lung tissue after the exposure of 0 ppm (CG), 20 ppm (LG) and 50 ppm (HG) ammonia for 30 days. Compared with the control group, the obvious lung lesions were observed in HG, including interstitial thickening, inflammatory cell infiltration and focal hemorrhage. The significantly increased content of malondialdehyde in HG, combined with the significantly decreased mRNA expression of antioxidase and inflammatory‐regulators in exposure groups, implied that ammonia exposure induced oxidative stress and diminished the anti‐inflammatory response in lung tissues. Metabolomic analyses of lung tissues revealed 15 significantly altered metabolites among the three groups including multiple amino acids, carbohydrates and lipids. The accumulation of succinic acid, linoleic acid and phosphorylethanolamine and consumption of glucose, quinolinic acid and aspartic acid in ammonia exposure groups, indicated that energy supply from glucose aerobic oxidation was suppressed and the glycolysis and lipolysis were activated in lung tissues induced by chronic ammonia exposure.